2000
DOI: 10.1093/bja/85.2.242
|View full text |Cite
|
Sign up to set email alerts
|

Altered globe dimensions of axial myopia as risk factors for penetrating ocular injury during peribulbar anaesthesia

Abstract: We measured the range of equatorial horizontal widths (EHW) in axially myopic eyes and identified the sites of staphyloma using B scan echography. One hundred eyes in 50 patients were studied. The axial lengths (ALs) were sorted into five groups of increasing severity of myopia. The group mean AL, group mean EHW and the ratio of EHW/AL was calculated for each range. The results suggest that the increase in the AL in an axially myopic eye is associated with an increase in the EHW. However, this increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…The axial length, horizontal length, vertical length, and volume of the highly myopic eyes were greater than those of the emmetropic eyes, with the axial length obviously increasing more than the vertical and the horizontal lengths. These findings are similar to those made by Vohra and Good [23] and suggest that the expansion of highly myopic eyes might be predominantly axial. The amplification of the horizontal length was less pronounced than that of the vertical length, a finding that differs from the results of Atchison et al [24,25] .…”
Section: Discussionsupporting
confidence: 91%
“…The axial length, horizontal length, vertical length, and volume of the highly myopic eyes were greater than those of the emmetropic eyes, with the axial length obviously increasing more than the vertical and the horizontal lengths. These findings are similar to those made by Vohra and Good [23] and suggest that the expansion of highly myopic eyes might be predominantly axial. The amplification of the horizontal length was less pronounced than that of the vertical length, a finding that differs from the results of Atchison et al [24,25] .…”
Section: Discussionsupporting
confidence: 91%
“…Many techniques—x-ray tomography,45 B-scan ultrasonography,46 computed tomography,47 optical coherence reflectometry,48 MRI2325,49—have been used to compare eye shape and refractive error in humans. Although there is substantial variability in eye shape between subjects, between studies, and within a given refractive error group, there is general agreement that the eyes of humans with emmetropia are typically oblate and that the eyes of those with myopia have larger equatorial (horizontal) diameters and much longer axial lengths.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated changes in eyeballs according to elongation of AL, a cause of axial myopia. Vohra and Good [2] suggested that expansion of highly myopic eyes may be predominantly axial rather than global, at least when compared in the horizontal meridian. Zhou et al [3] reported that emmetropic eyes usually have similar lengths and widths, but that myopic eyes are greater in length than width and that the dimension differences increase quickly with increases in myopia.…”
Section: Introductionmentioning
confidence: 99%